(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
The serious effects that have, in general, natural resources and economic and social crisis that cross several countries, have revitalized the interest in an accelerated and sustained development of agriculture, which can only be achieved to the extent production strategies that are consistent with the rational use of the ecosystem. In this context, see the agricultural activities in agroforestry systems is a valid approach, necessary and current research and training in livestock development in the tropics. Agroforestry production systems are defined as a series of systems and technologies in land use that combines trees with crops and/or pasture, depending on the time and space to increase and optimize production steadily. These systems can help solve problems in the use of natural resources due to biological and socio-economic functions they perform. From the biological point of view, the presence of trees encourages production systems in areas such as maintaining nutrient cycling and increased species diversity. In addition, because the vertical structure provided by trees and other woody plants and crops can coexist with different light requirements, also, the trees protect the soil from sun, wind and heavy rains that characterize the tropics. The use of agroforestry can also provide economic and sociocultural benefits, among which we can mention the reduction of economic risks by diversifying production and creating new jobs in nursery work, planting, maintenance areas, etc. Early attempts to define agroforestry back to 1977-1979, Combe and Budowski described it as "a set of land management techniques, which involve the combination of forest trees, either livestock or crops." However, the word came into our language Agroforestry English from agroforestry, so in recent years have expressed various views about the true definition of the concept. He has been using the words interchangeably agroforestry, agroforestry systems, agrodasonomy and agroforestry, among others. In developing this article will review the terms of use agroforestry and agroforestry systems, because they are widely used in the literature review to define agroforestry techniques. It is also necessary to clarify that agroforestry systems will be addressed more closely related to agricultural crops and their combinations, because in previous years, published an article in this magazine about silvopastoral systems for cattle.